2020
DOI: 10.1073/pnas.1916251117
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of male pregnancy associated with remodeling of canonical vertebrate immunity in seahorses and pipefishes

Abstract: A fundamental problem for the evolution of pregnancy, the most specialized form of parental investment among vertebrates, is the rejection of the nonself-embryo. Mammals achieve immunological tolerance by down-regulating both major histocompatibility complex pathways (MHC I and II). Although pregnancy has evolved multiple times independently among vertebrates, knowledge of associated immune system adjustments is restricted to mammals. All of them (except monotremata) display full internal pregnancy, making evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
128
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 100 publications
(168 citation statements)
references
References 62 publications
13
128
1
Order By: Relevance
“…We assessed the robustness of our divergence-time estimates with a range of re-analyses that were identical to those with the “strict” dataset except that (1) MCMC sampling was done without data, only from the prior distributions; (2) all cichlid fossils were excluded; (3) the fossil sampling rate assumed for CladeAge calibrations was doubled or halved; (4) the net diversification rate assumed for calibrations was doubled or halved; or (5) the interrelationship of Osteoglossomorpha, Elopomorpha, and Clupeocephala (all remaining teleosts) was constrained so that Osteoglossomorpha were either the sister group to Elopomorpha 14 , 74 or to Clupeocephala 12 , 19 .…”
Section: Methodsmentioning
confidence: 99%
“…We assessed the robustness of our divergence-time estimates with a range of re-analyses that were identical to those with the “strict” dataset except that (1) MCMC sampling was done without data, only from the prior distributions; (2) all cichlid fossils were excluded; (3) the fossil sampling rate assumed for CladeAge calibrations was doubled or halved; (4) the net diversification rate assumed for calibrations was doubled or halved; or (5) the interrelationship of Osteoglossomorpha, Elopomorpha, and Clupeocephala (all remaining teleosts) was constrained so that Osteoglossomorpha were either the sister group to Elopomorpha 14 , 74 or to Clupeocephala 12 , 19 .…”
Section: Methodsmentioning
confidence: 99%
“…1 , Figshare: Dataset 1 ). All seahorses are sedentary but exhibit specialized morphological and life-history traits 11 13 , such as a prehensile tail (and the lack of a caudal fin), an elongated snout, lack of pelvic fins, an armor of bony plates instead of scales, and a unique mode of male pregnancy whereby males give birth to developed juveniles 14 , 15 . Species of seahorses differ widely in body size, color patterns and other adaptive traits to their respective environments 11 , such as the presence or absence of bony spines, which are likely an adaption against predators 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Targeted assembly was conducted with Kollector v.1.0.1 [99], using marker sequences of Gadus morhua from Roth et al [98] as queries. From the set of whole-genome and targeted assemblies, candidate orthologs to the 3,061 exon markers used by Roth et al [98] were then identified through TBLASTN searches, using sequences of Danio rerio as queries as in the earlier study. The identified sequences were aligned with MAFFT and filtered to exclude potentially remaining paralogous sequences and misaligned regions: We removed all sequences with TBLASTN bitscore values below 0.9× the highest bitscore value and all sequences that had dN/dS values greater than 0.3 in comparison to the Danio rerio queries, we removed codons from the alignment for which BMGE v.1.1 [100] determined a gap rate greater than 0.2 or an entropy-like score greater than 0.5, and we excluded exon alignments with a length shorter than 150 bp, more than two missing sequences, or a GC-content standard deviation greater than 0.04.…”
Section: Discussionmentioning
confidence: 99%